Traumatic Thrombosis of the Intra-Petrous and Cavernous Segment of the Internal Carotid Revealed by Otological Symptoms: A Case Report - Rochd, Sara; Benhoummad, Othmane; Rizkou, Fatimezzahra; Lakhdar, Youssef; Rochdi, Youssef; Raji, Abdelaziz (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Thrombosis of the internal carotid following a non-penetrating blunt trauma is rare and unusual, implicating mostly intimal and medial vessel wall damage. With the lack of proper clinical presentation, it’s often diagnosed by arteriography while searching for expansive cerebral hemorrhagic complications. Case report: Hence, the report of this rare case of a post blunt trauma thrombosis of the intra-petrous and cavernous segment of the internal carotid in a 26-years-old male patient was revealed 1 year later by otological symptoms. CT scan, MRI, and angiography confirmed the diagnosis. Conclusion: Management of this serious injury is controversial, to say the least among authors involving both medical and surgical treatment.